Does political issue matter in voting intention in Ghana? A political marketing perspective - Zakari Bukari; Abu Bakar Abdul Hamid; Hishamuddin Md. Som; George Cudjoe Agbemabiese; Fidelis Quansah (Cogent Business & Management, 2022)
Voters' participation is considered fundamental in an electoral process. Yet almost half the countries in the world have voter turnouts of (60-79) percent. To be able to predict and influences voters' behavior, political parties and political consultants need to identify determinants of voters' behavior. This study is pursued to identify the motivation behind a sample of voters who cast a ballot in the 2012 and 2016 presidential elections. Structural equation model Amos was used with a sample of 493 voters. The objective of this is to conceptualized a strategic direction and propose a framework for voters' behavior determinants. The findings revealed that political issue directly influences voting intention. The findings further established that; Voters' trust and loyalty mediate and moderate the relationship. We therefore recommended that, Management of the various political parties should pay particular attention to these political issue variables in their quest to influences voters' voting intention.
Keywords: 650; loyalty; political Issues; Trust; Voting Intention